2007
DOI: 10.1542/peds.2006-2742
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Congenital Heart Defects and Small for Gestational Age

Abstract: Infants with congenital heart defects are approximately twice as likely to be small for gestational age as control subjects. Small for gestational age status may affect clinical management decisions, therapeutic response, and prognosis of neonates with congenital heart defects. Although the etiology of growth retardation among infants with congenital heart defects is uncertain, further exploration may uncover a common pathogenesis or causal relationship between congenital heart defects and small for gestationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
95
3
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 37 publications
10
95
3
6
Order By: Relevance
“…The frequency of infants who were SGA (21.5%) is comparable to the rate (15.2%) reported in Malik et al, 14 which described an association between CHDs and SGA in a population-based study. However, we did not find SGA to be independently associated with hospital mortality.…”
Section: (33%)supporting
confidence: 82%
“…The frequency of infants who were SGA (21.5%) is comparable to the rate (15.2%) reported in Malik et al, 14 which described an association between CHDs and SGA in a population-based study. However, we did not find SGA to be independently associated with hospital mortality.…”
Section: (33%)supporting
confidence: 82%
“…The tissue and allele expression profile of DDC is broadly incompatible with the etiology of SRS, although it is noteworthy that a small number of SRS patients display cardiac defects as well as increased predisposition to congenital heart disease (16). Further studies to increase the number of human heart specimens tested for allele-specific expression would help decipher whether DDC expression in the developing heart, an organ that may indirectly influence fetal growth (35,41,56), could be involved in SRS at 7p12.2.…”
mentioning
confidence: 99%
“…(30) The latter study found the associations to be valid for all types of CHD tested. Their results did not show a statistically significant relationship between birth weight and incidence of CHD within the VLBW population, although this may have been due to the small numbers involved.…”
Section: Discussionmentioning
confidence: 78%